China‘s soft power and the Balkans - Obradović, Žarko (Sociološki pregled, 2022)
The People‘s Republic of China, along with the United States and the Russian Federation, has become a great power in international affairs as a result of its significant economic expansion in recent decades, as well as the strengthening of its military force and pronounced political influence. What distinguishes China in the global order is its developing soft power, which profiles it as a desirable partner for cooperation. In other words, China is economically and politically “present” in every corner of the world, and in the last decade, more than ever before in the Balkans. China‘s relations with the Balkan countries are improving and becoming more substantial, and they are most developed with Serbia. The paper will explore the elements of China‘s “soft power” and how it is used in cooperation with the Balkan countries, as well as the reasons that set Serbia apart in cooperation with China in relation to other Balkan countries. An attempt will be made to answer the questions about the benefits of the Balkan countries‘ cooperation with China, why the US and the EU have a negative attitude towards China‘s cooperation with the Balkan countries, and whether such a relationship is motivated solely by economic reasons or other geopolitical interests.